Activation and Decomposition of Methane over Cobalt‐, Copper‐, and Iron‐Based Heterogeneous Catalysts for COx‐Free Hydrogen and Multiwalled Carbon Nanotube Production. Issue 8 (20th February 2017) - Dasireddy, Venkata D. B. C.; Likozar, Blaž
Abstract: Monometallic 50 wt % Cu/Al2 O3 catalyst and bimetallic catalysts containing 25 wt % Co/25 wt % Cu, 25 wt % Co/25 wt % Fe, and 25 wt % Cu/25 wt % Fe, supported on Al2 O3, were prepared by impregnation and coimpregnation methods. For bimetallic catalysts, metal oxides were in the form of spinel oxides, which exhibited a strong metal–support interaction. The decomposition of methane over these catalysts led to the formation of pure hydrogen and carbon nanotubes on their surfaces. The activation energy, total carbon yield, and amount of hydrogen formed, by using the prepared catalysts, were in agreement with the metal dispersion and acid–base site ratio on the surface of the catalysts. Cu−Fe/Al2 O3 catalyst exhibited a stable hydrogen formation rate of 58 mmol min −1 g −1 at a temperature of 650 °C. All catalysts exhibited deactivation after 500 min, which occurred due to the formation of carbon on the surface of the catalysts. The carbon material deposited predominantly assumed the form of multiwalled carbon nanotubes, as evidenced by high‐resolution TEM and Raman spectroscopy. Thermogravimetric analysis finally confirmed that Cu−Fe/Al2 O3 exhibited a higher yield of multiwalled carbon nanotubes. Abstract : Break it down ! Methane decomposition over bimetallic catalysts to produce carbon‐free hydrogen: Adding cobalt or iron to monometallic copper enhances strong metal–support interactions. The Cu−Fe/Al2 O3 catalyst exhibits a stable hydrogen formation rate. All catalysts produce hydrogen and form carbon nanotubes at high temperature and long exposure times.